Analysis of resistance genes in pan-resistant Myroides odoratimimus clinical strain PR63039 using whole genome sequencing. (November 2017) - Ming, De-song; Chen, Qing-qing; Chen, Xiao-tin
Abstract: To clarify the antibiotic resistance mechanisms of Myroides odoratimimus, pan-resistant M. odoratimimus strain PR63039 was isolated and its genome sequenced and analyzed. Antimicrobial susceptibility testing was conducted using the Kirby-Bauer disk diffusion method, and the Phoenix-100 Automated Microbiology System with a NMIC/ID-4 panel including aminoglycosides, β-lactams, polypeptides, quinolones, sulfonamides, chloramphenicols, and tetracyclines. Single-molecule real-time whole genome sequencing was conducted using the PacBio RSII system, and genome annotation was performed using RAST and IMG ER. To characterize the genome features, a number of databases and software programs, including GC-Profile, CG viewer, the VFDB database, ISfinder, RADB, CARD, ResFinder, and PHAST, were used. M. odoratimimus isolate PR63039 was resistant to almost all antibiotics tested, suggesting pan-drug resistance. The genome consisted of a 4, 366, 950-bp chromosome and a 90, 798-bp plasmid (p63039), which contained a large number of resistance genes and virulence factors. The distribution of the resistance genes was distinctive, and a resistance region, designated MY63039-RR, was identified. RAST analysis indicated that 108 of the annotated genes were potentially involved in virulence, disease, and defense, all of which could be associated with resistance and pathogenicity. Prophage analysis also identified two incomplete prophages in the genome of M. odoratimimus PR63039. Multiple antibiotic-resistance genes were identified, including those associated with resistance to tetracycline ( tetX ), macrolides ( ereB, cfrA, lasE ), sulfonamides ( sul2, sul3 ), β-lactams ( bla MUS-1, bla TUS-1, bla SFB-1, bla SLB-1, bla OXA-209, bla OXA-347 ), and chloramphenicol ( cat ). Further, the presence of 18 antibiotic efflux pump-encoding resistance genes, including acrB, acrD, acrF, adeB, adeG, adeJ, amrB, ceoB, cmeB, mdsB, mexB, mexD, mexF, mtrD, smeE, mdtF, macB, likely accounts for the observed quinolone resistance of strain PR63039. To the best of our knowledge, this is the first report of the presence of the bla SFB-1, bla SLB-1, bla OXA-209, bla OXA-347, and tetX resistance genes in M. odoratimimus. Highlights: We determined the complete genome sequence of a clinical pan-resistant M. odoratimimus strain PR63039. The M.odoratimimus genome consists of chromosome (GenBank no.CP013690 and no.CP013691 ) and a plasmid p630. The M.odoratimimus genome contains many resistance genes, including beta-lactamase, tetX, EreB, cfrA, lasE, sul2, sul3, cat. This is the first report of presence of the SFB-1, SLB-1, OXA-209, OXA-347, tetX resistance genes in M. odoratimimus.